Climate-Driven Changes in High-Intensity Wildfire on Orbital Timescales in Eurasia since 320 ka - Tianze Cheng; Jianjun Zou; Xuefa Shi; Sergey Gorbarenko; Yuriy Vasilenko; Alexandr Bosin; Yanguang Liu; Bing Chen (Lithosphere, 2022)
AbstractWildfire is an integral part of the Earth’s climate system and plays an important role in shaping terrestrial ecosystems and biodiversity, atmospheric chemistry, regional climate, and the carbon cycle in the Earth’s history. However, the lack of high-resolution records of long wildfires limits our understanding of the natural variability, long-term trends of wildfire activity, and the reasons behind the changes in wildfire on orbital timescales. Here, a 320 ka long high-resolution wildfire record from the subarctic North Pacific is reconstructed with black carbon (BC), including its two subtypes char and soot. A 7-day-long back trajectory simulation analysis reveals the higher frequency of trajectories comes from Siberia. Our data show that continuous incidence of wildfire on a continental scale over the last 320 ka was higher during glacial periods than during the interglacial periods. The increase in wildfire frequency during glacial periods is ascribed to less precipitation. Contrasting patterns of wildfire incidence between marine isotope stages 2 and 6 may be ascribed to different fuel availability, which is related to contrasting configurations of the Northern Hemisphere ice sheet between glacial periods. A significant periodicity of 23 ka of our wildfire record suggests the precession of the Earth’s orbit pace wildfire development. The tight coupling of intensified wildfire and enhanced nutrient utilization efficiency suggests a nontrivial role of fire in the climate system.